2015
DOI: 10.1371/journal.pone.0134911
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Transcriptional Profiles of Melanocytes from Dark and Light Skinned Individuals under Basal Conditions and Following Ultraviolet-B Irradiation

Abstract: We analysed the whole-genome transcriptional profile of 6 cell lines of dark melanocytes (DM) and 6 of light melanocytes (LM) at basal conditions and after ultraviolet-B (UVB) radiation at different time points to investigate the mechanisms by which melanocytes protect human skin from the damaging effects of UVB. Further, we assessed the effect of different keratinocyte-conditioned media (KCM+ and KCM-) on melanocytes. Our results suggest that an interaction between ribosomal proteins and the P53 signaling pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 61 publications
(60 reference statements)
3
11
0
Order By: Relevance
“…keratinocytes, immune cells, and melanocytes, to be taken into account. We note that in a study of UVR-treated cultured melanocytes, ribosome metabolism was the most significantly altered pathway at 6, 12, and 24h after UVR (39), as in our whole skin studies. To gain a better sense of changes in skin correlated with RRP15 expression we constructed a network of genes correlated with RRP15 expression across the sun-exposed anatomical site human skin GTEx cohort (Fig 5B).…”
Section: Skin Gene Expression Changes After Neonatal Uvrsupporting
confidence: 70%
“…keratinocytes, immune cells, and melanocytes, to be taken into account. We note that in a study of UVR-treated cultured melanocytes, ribosome metabolism was the most significantly altered pathway at 6, 12, and 24h after UVR (39), as in our whole skin studies. To gain a better sense of changes in skin correlated with RRP15 expression we constructed a network of genes correlated with RRP15 expression across the sun-exposed anatomical site human skin GTEx cohort (Fig 5B).…”
Section: Skin Gene Expression Changes After Neonatal Uvrsupporting
confidence: 70%
“…ROS have been shown to activate proinflammatory and MAPK signaling cascades, subsequently leading to various biological responses including cell death or dysfunction [4345]. López et al, reported that paracrine protective effects of CM from UVB-irradiated KC on MC involved regulation of various signaling pathways including proinflammatory and p53-dependent apoptotic pathways [42]. Our study demonstrated that the microenvironment created by KC reversed damaging effects of UVB on MC by reducing activation of caspase-3 and p53 that play a crucial role in UVR-mediated apoptosis associated with DNA damage [25,26], and by downregulating inflammatory markers including NF-κB activation and TNF-α levels implicated in photodamaged skin [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, López et al conducted a time-series analysis to compare the transcriptional profile of dark and light melanocyte lines under basal conditions and after UVB radiation, finding that ribosomal proteins can interact with the p53 signaling pathway in response to UVB [28]. This study identified a total of 151 up-regulated and 64 down-regulated genes in skin in response to UVB irradiation, which probably remained increased after repetitive exposure for approximately 2–3 weeks [11].…”
Section: Discussionmentioning
confidence: 99%